THE SCIENTIFIC HERITAGE OF ACADEMICIAN N.I. VAVILOV IN VEGETABLE CROP BREEDING AND GENETICS AT THE ALL-RUSSIAN RESEARCH INSTITUTE OF VEGETABLE BREEDING AND SEED PRODUCTION (VNIISSOK) - V. F. Pivovarov; N. I. Timin; L. Yu. Kan (Вавиловский журнал генетики и селекции)
The main ideals of N.I. Vavilov’s studies and their use in vegetable crop breeding and genetic research conducted at the All-Russia Research Institute of Vegetable Breeding and Seed Production are reviewed.